Conservation Status of the Family Orchidaceae in Spain Based on European, National, and Regional Catalogues of Protected Species - Daniel de la Torre Llorente (The Scientific World Journal)
This report reviews the European, National, and Regional catalogues of protected species, focusing specifically on the Orchidaceae family to determine which species seem to be well-protected and where they are protected. Moreover, this examination highlights which species appear to be underprotected and therefore need to be included in some catalogues of protection or be catalogued under some category of protection. The national and regional catalogues that should be implemented are shown, as well as what species should be included within them. This report should be a helpful guideline for environmental policies about orchid’s conservation in Spain, at least at the regional and national level. Around 76% of the Spanish orchid flora are listed with any figure of protection or included in any red list, either nationally (about 12–17%) or regionally (72%).